Analisis Pengelolaan Dana Desa di Desa Klenang Lor Kecamatan Banyuanyar Kabupaten Probolinggo - Najmi Nurul Ummah; Rahma Rina Wijayanti (Politeknik Negeri Jember, 2022)
This study aims to analyze the management of village funds in Klenang Lor Village, Banyuanyar District, Probolinggo Regency. This research is included in qualitative research. The data used are primary data and secondary data. Primary data in the form of interviews and secondary data see the required documents. The data collection procedure used the method of observation, interviews, documentation. The data analysis technique used is the comparative analysis method. This research is guided by Permendagri Number 20 of 2018 and Perbup Number 63 of 2019. Based on Probolinggo Regent Regulation Number 63 of 2019 concerning guidelines and supervision of Village Fund Management, to provide adequate confidence in the process of fostering and supervising Village Fund management through the planning stages, implementation and reporting. The results of this study indicate that the Village Fund Management in Klenang Lor Village in the planning, implementation, reporting stages is in accordance with the Regulation of the Minister of Home Affairs (Permendagri) Number 20 of 2018. Penelitian ini bertujuan untuk menganalisis pengelolaan dana desa di Desa Klenang Lor Kecamatan Banyuanyar Kabupaten Probolinggo. Peneltian ini termasuk dalam penelitian kualitatif. Teknik pengumpulan data diperoleh melalui observasi, wawancara, dokumentasi. Data yang digunakan yaitu data primer dan data sekunder. Teknik analisis data yang digunakan adalah metode analisis komparatif. Penelitian ini berpedoman pada Permendagri Nomor 20 tahun 2018 dan Perbup Nomor 63 tahun 2019. Berdasarkan Peraturan Bupati Probolinggo Nomor 63 tahun 2019 tentang pedoman dan pembinaan pengawasan Pengelolaan Dana Desa. Pedoman ini untuk memberikan keyakinan yang memadai terhadap proses pembinaan dan pengawasan pengelolaan Dana Desa melalui tahapan perencanaan, pelaksanaan serta pelaporan. Hasil penelitian ini menunjukkan bahwa Pengelolaan Dana Desa di Desa Klenang Lor dalam tahap perencanaan, pelaksanaan, pelaporan telah sesuai dengan Peraturan Menteri Dalam Negeri (Permendagri) Nomor 20 tahun 2018.